2D and 3D simulations of dynamic delamination in curved unidirectional CFRP laminates subjected to moment/axial combined loading. (15th July 2021) - Ata, Tamer Tahir; Coker, Demirkan
Abstract: Dynamic failure of 30-ply curved unidirectional CFRP laminate under quasi-static moment/axial combined loading used in the experiments of Tasdemir (2018) is investigated numerically. 2D and 3D explicit finite element analyses are carried out using cohesive zone elements and contact interactions to simulate progressive delamination. In both analyses, dynamic delamination initiates at the maximum radial stress location. The resultant crack propagation in both 2D and 3D simulations is observed to be intersonic in the arm regions, with lower crack tip speeds observed for the 3D case. In 3D simulations, a non-uniform crack front is observed, with the crack nucleating at the middle of the width, propagating to the edges and both arms at sub-Rayleigh speed before continuing to propagate in the arms at intersonic speeds. Intermittent local contact regions are observed in 2D simulations behind the crack tip, which are also observed in the 3D simulations at the free edge with a continuous contact line reaching the middle of the crack front, emphasizing the three-dimensional nature of the delamination growth. Load-displacement curves of both 2D and 3D simulations show good correlations with experimental results.